Numerical Study of Three-Phase Liquid-Gas-Solid Flow in Single and Group Hydrocyclones - Murodil Madaliev; Zokhidjon Abdulkhaev; Aybek Arifjanov; Khamidulla Mamatov; Mushtariybonu Gafforova (Journal of Mechanical Engineering)
In this paper, numerical modeling and analysis of the efficiency of a single hydrocyclone HC-800 and a group hydrocyclone HC-400x4 are performed using the Ansys Fluent software package. The VOF (Volume of Fluid) method, designed to simulate multiphase flows, is used to model hydrodynamic processes. The SST GEKO model, which has proven itself in working with swirling flows due to its accuracy and stability, is used as a turbulence model. The calculations are carried out at the same capacity of 350 m³/h, which makes it possible to directly compare the efficiency of both types of hydrocyclones. Numerical data confirm that the group hydrocyclone HC-400x4 demonstrates significantly higher separation efficiency compared to a single hydrocyclone HC-800.